2022
DOI: 10.1007/s41027-022-00374-w
|View full text |Cite
|
Sign up to set email alerts
|

Bengali Migrant Workers in South India: A Mixed-Method Inquiry into Their Earnings, Livings and Struggle During Covid Pandemic

Abstract: This study has tried to compare the earning and non-earning aspects of migrant workers from West Bengal engaged in different types of work in Karnataka and Kerala based on survey of 111 Bengali-speaking migrant workers and a number of in-depth interviews and FGDs. The study has found that most of the migrant workers landed in south India only after working in Kolkata, northern or western Indian cities. Lack of regular employment opportunities and low-wage rate in rural as well as urban West Bengal are the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Religious tolerance is indispensable for the inclusivity targeted by SDG 11, as well as for the reduction of inequalities targeted by SDG 10. Chakraborty et al (2022), in their interactions with ragpickers in southern India, found that the locals were earning more than the migrants from eastern India; and the Hindus more than the Muslims. The latter felt discriminated against, presumably on religious/linguistic grounds, as was also observed by Murthy (2016) in northern India.…”
Section: Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…Religious tolerance is indispensable for the inclusivity targeted by SDG 11, as well as for the reduction of inequalities targeted by SDG 10. Chakraborty et al (2022), in their interactions with ragpickers in southern India, found that the locals were earning more than the migrants from eastern India; and the Hindus more than the Muslims. The latter felt discriminated against, presumably on religious/linguistic grounds, as was also observed by Murthy (2016) in northern India.…”
Section: Educationmentioning
confidence: 99%
“…It is up to the governments at all levels eventually to redress grievances on a continuous basis, through effective, long-overdue policy changes (Chandramohan et al 2010;Ravindra et al 2016;Rawat et al 2018;Masood et al 2020;Chakraborty et al 2022). Florin (2015), by highlighting the efforts taken by the Egyptian government to recognise the important role played by rag-pickers in the country's socio-economic development, has indirectly signalled to the governments of other countries in the developing world to follow suit, by at least having a good social protection system in place for migrant/itinerant rag-pickers [emphasized by Chakraborty et al (2022) in their study of Bengali migrant workers in south India]. Indeed, there is never any silverbullet solution, and oftentimes, policies which are in place at local levels, may not be implemented religiously.…”
Section: Who Are Being Addressed and Why?mentioning
confidence: 99%
See 3 more Smart Citations